Relationship between internet addiction and academic performance of undergraduate medical students of Azad Kashmir - Javaeed, Arslaan (Pak J Med Sci, 2020)
OBJECTIVE: To assess the relationship between internet addiction (IA) and academic performance among the medical students of Azad Kashmir, Pakistan. METHODS: A cross-sectional study was done involving 316 medical students of Poonch Medical College, Azad Kashmir, Pakistan from May 2018 to November 2018. Dr. Young’s Internet Addiction Test questionnaire was used as the tool of data collection. The questionnaire contained twenty 5-points Likert scale questions to assess internet addiction. IA score was calculated and the association between IA and academic performance was observed by Spearman Rank Correlation test. Relationship between baseline characteristics of the medical students and IA was also seen. RESULTS: Eighty-nine (28.2%) medical students fell under the category of ‘severe addiction’ and most importantly only 3 (0.9%) were not internet addicted according to Dr. Young’s questionnaire. Internet addicted medical students scored significantly poor in their exams (p. <.001). One hundred thirty one (41.4%) students with a median IA score of 45 scored in the range of 61-70% marks as compared to 3 (0.9%) students with a median IA score of 5, secured greater than 80% marks. CONCLUSION: This study and many other previous studies have revealed that internet addiction affects academic performance. The number of internet users is ever increasing therefore, the number of internet misusers will also increase. If no step is taken to control internet addiction, it may cause a serious impact in the future.